A Highly Sensitive Plasmonic DNA Assay Based on Triangular Silver Nanoprism Etching - Yang, Xinjian; Yu, Yuebo; Gao, Zhiqiang (ACS nano, 2014)
Specific nucleic acid detection by using simple and low-cost assays is important in clinical diagnostics, mutation detection, and biodefense applications. Most current methods for the quantification of low concentrations of DNA require costly and sophisticated instruments. Here, we have developed a facile DNA detection platform based on a plasmonic triangular silver nanoprism etching process, in which the shape and size of the nanoprisms were altered accompanied by a substantial surface plasmon resonance shift. Through the combination of enzyme-linked hybridization chain reaction amplification and inherent sensitivity of plasmonic silver nanoprims, this assay could detect as low as 6.0 fM target DNA. Considering the high sensitivity and selectivity of this plasmonic DNA assay, it is expected to be of great interest in clinical diagnostics.